2016
DOI: 10.12688/f1000research.7579.1
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling in cancer stem cells and colon cancer metastasis

Abstract: Overactivation of Wnt signaling is a hallmark of colorectal cancer (CRC). The Wnt pathway is a key regulator of both the early and the later, more invasive, stages of CRC development. In the normal intestine and colon, Wnt signaling controls the homeostasis of intestinal stem cells (ISCs) that fuel, via proliferation, upward movement of progeny cells from the crypt bottom toward the villus and differentiation into all cell types that constitute the intestine. Studies in recent years suggested that cancer stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
144
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(150 citation statements)
references
References 90 publications
(125 reference statements)
1
144
0
5
Order By: Relevance
“…The critical feature of CSCs is self-renewal, which is responsible for cancer drug resistance, metastasis, and recurrence [19, 20, 45]. We found that Lgr5-positive subpopulations generated significantly more multipotent spheres than did Lgr5-negative subpopulations, indicating a remarkable self-renewal advantage of Lgr5-positive cells.…”
Section: Discussionmentioning
confidence: 87%
“…The critical feature of CSCs is self-renewal, which is responsible for cancer drug resistance, metastasis, and recurrence [19, 20, 45]. We found that Lgr5-positive subpopulations generated significantly more multipotent spheres than did Lgr5-negative subpopulations, indicating a remarkable self-renewal advantage of Lgr5-positive cells.…”
Section: Discussionmentioning
confidence: 87%
“…The canonical Wnt pathway is an evolutionarily conserved mechanism of stem cell regulation [24, 25]. Aberrant regulation of the Wnt pathway causes malignant proliferation, and its activation helps maintain the CSC reservoir that contributes to CRC stemness, recurrence, and chemoresistance [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Aberrant regulation of the Wnt signaling pathway is known to play a role in tumorigenesis and maintenance of cancer stem cells. 3,4,28 The Wnt pathway can be activated aberrantly not only by mutations of genes functioning in Wnt signaling such as APC and CTNNB1 but also by dysregulation of secreted antagonists. For example, diminished expression caused by promoter methylation of Wnt antagonists genes sFRP1 and WIF1 results in unregulated increase of ligand-dependent Wnt signaling activity.…”
Section: Discussionmentioning
confidence: 99%